The cost of the 2011 general elections in Nigeria (2012)
This article examines the cost of the 2011 general elections in Nigeria in real and financial terms. It reviews the regulatory framework for financing the elections and attempts to estimate the costs, drawing on figures and reports published by the Independent National Electoral Commission (INEC) and reports relating to the financial activities of political parties, candidates and other politicians. It estimates the cost to have been about N566.2-billion,1 representing about 2% of the gross domestic product. This figure does not include party and campaign financing. The article explores other, nonmonetary, costs, including the loss of life and property in the violence that followed the elections, and concludes that the cost of the elections was too high for the sustenance of democracy. Hopeful that future elections will cost less, it offers suggestions about ways of reducing costs without impinging on the integrity of elections